Measuring the Level of Physical Condition of the Remba FC Bangkalan Futsal Club - Arifin, Sulthon; Himawan, Agus; Purwoto, Septyaningrum Putri (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to measure the level of physical condition of Remba FC Bangkalan Futsal Club players based on the five main components of physical fitness, namely endurance, strength, flexibility, speed and agility. This research uses a quantitative descriptive method with a survey approach. The population in this study were all active players of the Remba FC Club, with a sample of 10 people selected using a purposive sampling technique based on the criteria of age 19 years and activeness in training. The research instruments consisted of five types of standardized physical tests: 1200 meter running test (endurance), sit-up test (strength), sit and reach test (flexibility), 60 meter sprint test (speed), and shuttle run (agility). The data analysis technique used is descriptive statistics in the form of frequency distributions and percentages based on the classification of Indonesian Physical Fitness Norms. The research results show that in general the players' physical fitness levels are in the Good (50%), Very Good (30%), and Medium (20%) categories. Specifically, strength and agility have dominant values in the Very Good category, while endurance and speed show a distribution of values that still needs to be improved. These results show that even though the players' physical condition is quite good, strengthening special training programs in the aspects of endurance and speed is still very necessary to support optimal performance in matches.